"I Want to Leave ASAP": Black Women Teachers Discuss the Role of Administrative Support and Teacher Turnover. Issue 3 (May 2021) - Stanley, Darrius A.
This article utilizes a qualitative case study methodology informed by a Black feminist theoretical lens to explore the experiences of Black women teachers, administrative support, and teacher turnover. Five self-identified Black women teachers discuss the impact that school leaders have on their decisions to leave their schools. Three common leadership practices emerged as contributory factors that influence teacher turnover: (a) arresting social justice efforts, (b) insufficient support for discipline, and (c) relationships with administration. This article concludes with a discussion about the requisite school leader philosophical orientations that support the unique needs of Black women teachers.